Potential biomarkers in personality disorders : current state and future research (2016)
ABSTRACT: This review article presents the most appropriate strategies for examining the phenotype for personality disorders. At present there are many neurobiological and molecular studies that suggest a genetic predisposition to different traits representative of expressed personality disorders. Nonetheless, it has not been possible to accurately and successfully replicate such results due to some difficulties regarding the sensitivity, specificity and validity of the clinical evaluation methods, and the size and type of the chosen population and experimental designs used for research. Unfortunately, diagnoses done in psychiatry and psychology have a classification system based on the prevalence and intensity of symptoms and do not take into account the etiology, neurobiology, epidemiology, genetics, and drug responses. On the other hand, explaining the phenomenology of personality disorderes and how genes work together to express this phenotype implies a revision of the chaos theory, addressing the connection between neurodevelopment, significantly stressful events during early childhood and epigenetic modifications in DNA related to stochastic events which may contribute to the development of normal or abnormal behavior.